Investment in the Development of Latvian Music Pedagogy by Latvians Living beyond Latvia - Sīle, Maruta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
History of music pedagogy is developed by great personalities. Wherever Latvia’s musicians have been brought by their life routes – music has been above any difficulties encountered. The artist’s education has to be represented in two directions – historical and systematic. Without a clear insight into one’s own national history of art, no one can grow into a real artist. Explorations in history of music pedagogy can more objectively assess the present and prognosticate perspectives in the future. The more we learn about the Latvian by descent artists’ creative activities, their working methods and results beyond Latvia, the greater is our desire to use their experiences in our own work, as the child development is always in the centre of researches. One of collaboration ways is the’’ International Latvian Young Musicians Camp’’ headed by the director – professor, Dr.paed. Ingrīda Gutberga, a Latvian living abroad, well-known as an organist, conductor, pianist, chair person of Boston Latvian Heritage foundation. The participants of the camp are young musicians from all over the world enjoying guidance of internationally renowned music pedagogues.